Short-term exposure to dexamethasone promotes autonomic imbalance to the heart before hypertension - Duchatsch, Francine [UNESP]; Constantino, Paula B. [UNESP]; Herrera, Naiara A. [UNESP]; Fabrício, Mayara F. [UNESP]; Tardelli, Lidieli P. [UNESP]; Martuscelli, Aline M. [UNESP]; Dionísio, Thiago J.; Santos, Carlos F.; Amaral, Sandra L. [UNESP] (Elsevier, 2018)
Hypertension is one of the chronic side effects of dexamethasone (DEX) treatment; however, almost nothing is known about its acute effects. Therefore, the aim of this study was to investigate the possible mechanisms involved in blood pressure control after acute or short-term DEX treatment in adult animals. Eighty Wistar rats were divided into four groups: C1 and C5, for rats treated with saline for 1 or 5 days, respectively; D1 and D5, for rats treated with DEX for 1 or 5 days, respectively (decadron, 1 mg/kg, i.p.). Heart rate was increased in DEX treatment, but arterial pressure and cardiac muscle mass were not altered. Only few and isolated changes on gene expression and protein level of renin-angiotensin system components were observed. Five days of DEX treatment, but not one day, determined an increase in sympathetic component of spectral analysis (+75.93%, P <.05) and a significant reduction of parasympathetic component (–18.02%, P <.05), which contributed to the autonomic imbalance to the heart (LF/HF, +863.69%). The results of this present study demonstrated, for the first time, that short-term exposure to DEX treatment impairs the autonomic balance to the heart before hypertension, which was independent of renin-angiotensin system.
Keywords: Autonomic nervous system; blood pressure; glucocorticoids